Adipogenic differentiation potential of adipose‐derived mesenchymal stem cells from ovariectomized mice. (9th September 2014) - Fu, Y.; Li, R.; Zhong, J.; Fu, N.; Wei, X.; Cun, X.; Deng, S.; Li, G.; Xie, J.; Cai, X.; Lin, Y.
Abstract Objectives In human post‐menopausal osteoporosis, enhanced adipogenesis in bone marrow and enhanced formation of adipose tissue in vivo are observed. These changes correlate with reduced trabecular bone volume and increased adipocyte cell size as well as cell number. However, cellular and molecular mechanisms underlying osteoporosis‐related changes in adipocyte cell volume are not known. This study was designed to compare adipogenic potential of adipose tissue‐derived stem cells (ADSCs) obtained from ovariectomized mice with that of control ADSCs, and to analyse pathological mechanisms from the point of functional changes of ADSCs. Materials and methods Healthy female C57BL/6J mice were randomly divided into ovariectomy and sham‐surgery groups. Mouse ADSCs were isolated and cultured in vitro up to passage 3. After adipogenic induction, oil red O staining of lipid droplets was used to detect adipogenic ability of ADSCs; real‐time PCR and immunofluorescence staining were used to detect expression of adipogenesis‐related genes and proteins. Results As indicated by increased expression of adipogenic and lipogenic genes and proteins, and lipid droplets accumulation shown by oil red‐O staining, adipogenic differentiation of ADSCs was significantly enhanced in the ovariectomy group compared to the sham‐surgery group (P < 0.05). Conclusion These findings suggest that enhanced adipogenic differentiation of ADSCs is likely to be the important cause for increased adipogenesis in vivo and subsequent obesity‐like changes in body mass, in mice, after ovariectomy.